(untitled) (Bangladesh Journal of Animal Science, 2022)
In “Chhana binders effects on the quality of Rosogolla” by Begum et al. (Bangladesh Journal of Animal Science, (2022), Volume 51, Issue 1, Page 12-16), there is an error in the identification of the authors “J Begum, MN Islam, MH Rashid, S Begum, MZ Islam, AL Shekh and MSR Siddiki*” and second line of authors affiliation “Gouripur Govt. College, Mymensingh, Bangladesh, 2District Election Officer, Netrokona, Bangladesh”. The authors name with proper identification should read “J Begum, MN Islam, MH Rashid, S Begum1, MZ Islam, AL Shekh2 and MSR Siddiki*” and the second line of the authors affiliation should read “1Gouripur Govt. College, Mymensingh, Bangladesh, 2District Election Officer, Netrokona, Bangladesh”. The editorial board regret the error.